EFFECT OF GESTATIONAL DIABETES AND MATERNAL HYPERTENSION ON GROSS MORPHOLOGY OF PLACENTA - Ashfaq, Muhammad; Janjua, Muhammad Zahoor; Channa, Muhammad Aslam (Journal of Ayub Medical College Abbottabad, 2005)
Background: Gestational diabetes is much more common than pre-existing diabetes i.e. it complicates 2% to 5% of pregnancies. When metabolic control is good, perinatal mortality should be no higher than in general population. However, macrosomia continuous to be a problem in higher than average proportions of such cases. Macrosomia also involves placenta within the chronic hypertensive disease, the most common diagnosis is essential vascular hypertension. Methods: Total 60 full term placenta, 20 from normal and 20 each from gestational diabetics and chronic hypertensive mothers were studied grossly. Shape, attachment of umbilical cord, weight, diameter and central thickness of all placentas were noted. Results: The study demonstrates that there is change of shape i.e. two lobes in one placenta from diabetic group. All other placentae were singly lobed and discoidal shape with central attachment of umbilical cord to the foetal surface of placenta. Weight central thickness and diameter were significantly greater in diabetic group as compared to normal and hypertensive group. Hypertensive group shows non significant decrease in weight of placentae while there was no change in central thickness and diameter of placenta in hypertensive than the normal group. Conclusions: On the basis of results of present study, it is concluded that diabetic's placentae showed increase in weight, central thickness and diameter. One out of 20 placentae in diabetic group also showed change of shape and attachment of umbilical cord to one love. Hypertensive's placentae showed no significant change in weight, shape central thickness and attachment of umbilical cord when compared with normal group. Key words: Placenta, Gestational diabetes, Maternal Hypertension.